A bean catching double pigeons: Sonication assisted modification of Nb2C MXenes composites by O-doping porous biomass-carbons for supercapacitors and zinc-ion batteries. (15th August 2023) - Yang, Wei; Yang, Zheng; Wang, Jing; Lu, Wei; Wang, Weihua
Abstract: MXenes materials are novel promising candidates for the next generation energy storage devices. In this work, we designed a facile avenue using biomass derived carbons (PCarbons) and Nb2 C MXenes as raw materials via sonication treatment to obtain Nb2 C-PCarbons composites (Nb2 C-PCarbons CPs). As a result, the prepared Nb2 C-PCarbons CPs achieved a relative high specific capacitance up to 465.6 F·g −1 in the three-electrode system with 6 M KOH electrolyte. The fabricated symmetric supercapacitors (SSCs) displayed the ultra-high energy density (126.9 Wh·kg −1 ) in ion liquid electrolyte and the long cycling life after 10, 000 cycles. Meanwhile, the obtained Nb2 C-PCarbons CPs were also applied as cathode materials in the aqueous zinc ion batteries (AZIBs), achieving the maximum discharge specific capacity of ca. 239.7 mAh·g −1 with good cycling stability. Thus, our work provides an efficient method to modify the MXenes as bi-functional materials for the potential high-value utilization in SSCs and AZIBs. Graphical abstract: A facile method was designed to obtain the well mixed Nb2 C-PCarbons composites by O-doped biomass carbons and Nb2 C MXenes via the long sonication process, which showed the excellent energy storage property for supercapacitors and zinc ion battery. Unlabelled Image Highlights: The Nb2 C-PCarbons composites (CPs) were prepared by a sonication assisted modification facilely. The O-doped biomass carbons enhanced the electrochemical property of Nb2 C MXenes effectively. Nb2 C-PCarbons CPs exhibited highest specific capacitance of 465.6 Fg −1 in KOH electrolyte. Nb2 C-PCarbons CPs/EMIMBF4 symmetric supercapacitors owned ultrahigh energy density (ED) of 126.9 Wh·kg −1 . The highest ED of Nb2 C-PCarbons CPs aqueous zinc-ion batteries was ca. 306.7 Wh·kg −1 .